Regional differences in the inflow of direct foreign investment into the Czech Republic - Hlaváček, Petr (Wewnętrzne relacje i kooperacja między regionami przygranicznymi, 2011)
This article analyses the inflow of foreign direct investment into the Czech Republic on the regional level. Their inflow shows a dynamic change. The early 1990s were represented by their low inflow and on the contrary, from the late 1990s to the time before the global economic crisis there was significant growth in direct foreign investment. From the regional point of view, Prague and the metropolitan regions of the Czech Republic with taking Mladá Boleslav region into special consideration dominate other Czech and Moravian regions in the context of direct foreign investment absorption.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2011; Nr 180, s. 153-160
Keywords: direct foreign investments; metropolitan area; region